MODULATION TECHNIQUE IN ENGLISH – INDONESIAN TRANSLATION OF JANE AUSTEN’S PRIDE AND PREJUDICE - Sofyansyah, Sofyansyah; Anita, Anita; Noverino, Romel (Universitas Gunadarma, 2017)
The aims of the research are: (1) to find out types of modulation technique applied in the translation of Jane Austen’s Pride and Prejudice, (2) to find out modulation techniques are most frequently used in the translation of Jane Austen’s Pride and Prejudice. The writer used descriptive analytical method in order to reach the aims of the research. The source of data is taken from a novel written by Jane Austen entitles Pride and Prejudice and its Indonesian translation by Berliani Mantili Nugrahani. The writer employs himself to collect data; by reading the novel and its translation, identifying the data, underlining and noting down, classifying, analyzing them based on theories of type of modulation translation technique. The findings of this research show that: from 92 data, the writer found 5 types of modulation technique, they are 72 negated contrary (78%), 14 abstract for concrete (15%), 3 interval to boundaries (4%), 2 term reversal (2%), 1 active to passive (1%). And the most frequently used of type of modulation technique is negated contary as many as 72 frequencies. Keywords: Translation, Translation Technique, Modulation